1987
DOI: 10.1007/bf00230145
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxide induced DNA damage: protection by turmeric (Curcuma longa)

Abstract: Liposomal lipid peroxidation and peroxide induced DNA damage were investigated. Inhibition of lipid peroxidation was studied using 400 microM uric acid, beta-carotene, alpha-tocopherol, curcumin and butylated hydroxyanisole (BHA). Curcumin, the active principle of turmeric (Curcuma longa), was as effective an antioxidant as BHA. An aqueous extract of turmeric was also found to be an effective inhibitor. The inhibition obtained using this aqueous extract, incorporated into the liposome itself, was 70% at 300 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…As a pure compound also, it has been found to possess antitumor, anti-cancer and anti-inflammatory activities. Several studies have clearly indicated that curcumin possesses a variety of pharmacological effects such as in wound-healing, 1) anti-oxidant [2][3][4] and anti-inflammatory activities. 5) Certain recent studies indicated that curcumin may exert its anti-inflammatory properties by: a) suppressing the activation of NF-kappaB through inhibition of IKK activity, 6) b) significantly inhibiting the LPS induced proinflammatory cytokines IL-1beta and IL-8 7) and c) inhibiting iNOS production and by scavenging NO radicals.…”
mentioning
confidence: 99%
“…As a pure compound also, it has been found to possess antitumor, anti-cancer and anti-inflammatory activities. Several studies have clearly indicated that curcumin possesses a variety of pharmacological effects such as in wound-healing, 1) anti-oxidant [2][3][4] and anti-inflammatory activities. 5) Certain recent studies indicated that curcumin may exert its anti-inflammatory properties by: a) suppressing the activation of NF-kappaB through inhibition of IKK activity, 6) b) significantly inhibiting the LPS induced proinflammatory cytokines IL-1beta and IL-8 7) and c) inhibiting iNOS production and by scavenging NO radicals.…”
mentioning
confidence: 99%
“…The well-established 4-nitroquinoline-l-oxide (4NQ0)-induced oral carcinogenesis model was used because oral lesions induced by 4NQ0 are more comparable to human lesions than those induced by other agents. We used aqueous extracts of turmeric instead of its lipophilic principle, curcumin, because the aqueous extract has been reported to have potent antioxidant activity [9,18]. Moreover, turmeric is consumed as a whole spice in a variety of food preparations in India.…”
mentioning
confidence: 99%
“…1), has been known to exert inhibitory actions on lipid peroxidation and DNA damage induced by reactive oxygen species (9)(10)(11)(12)(13). In this study, the treatment with curcumin at concentrations ranging from 300 nM to 3 pM significantly prevented thymocytes from cell death or injury caused by H202 induced oxidative stress (Fig.…”
Section: Discussionmentioning
confidence: 56%